Shear behaviour of jointed rockmass of sandstone quarry, Mizoram state, India - Singh T.N.; Monjezi M.; Sawmliana C.; Kumar S. (My University, 2025)
The shear behaviour of jointed rockmass in a sandstone quarry of south Hlimen, Mizoram were investigated for the slope stability analysis. A computer program was developed in 'C' language, to predict the shear strength and dilation of rock joints, based on Barton-Bandis Model. The program further helps to obtain field equivalents of physico-mechanical properties of such rock joints by using laboratory test data. Detailed joints survey were carried out in the field and basic geotechnical description (BGD) of the rockmass was described for rock joints as per recommendations of International Society for Rock Mechanics (ISRM). Tilt apparatus was used to determine the angles of tilt for the natural joint surfaces as well as for the smooth core samples. Jointwall compressive strength (JCS) and uniaxial compressive strength (UCS) of intact rock were also determined by using Schmidt's hammer. The present study showed that the shear behaviour of the rock joints influenced by many factors, among which joint roughness, level of normal effective stress and size of blocks (joint spacing) are of paramount importance.